(untitled) - Carter, Paul (New York, 1968)
A principal theme of the 1920s was "paradox," and Professor Carter explains the tensions that existed between city and country, progress and nostalgia for the past, progressive attitudes and the persistence of bigotry. Carter also provides incisive reevaluations of some archetypal figures of the era, such as Coolidge, Lindbergh, and Hemingway, and suggests new ways of considering events and developments such as jazz, popular sports, the Scopes trial, and isolationism.
Keywords: America,America,America; Economic conditions,History,Social aspects